Meningkatkan Kesadaran Kekerasan Seksual Dilingkungan Sekolah Menengah Atas (SMA) Negeri 5 Banjarmasin - Muhammad Agus Humaidi; Amelia Puspita; Ade Nur Atika Sari (Jurnal Pengabdian Masyarakat, 2025)
The socialization activity titled “Raising Awareness of Sexual Violence in the School Environment at SMA Negeri 5 Banjarmasin” aimed to provide students with knowledge and understanding that sexual violence is a serious violation of human rights and a major threat to the well-being and future of young people. This program was designed as a preventive effort to help students recognize, prevent, and confidently report acts of sexual violence or harassment that may occur in the school environment. The material delivered included an explanation of various forms of sexual violence, especially non-verbal harassment such as inappropriate comments, gestures, or actions that degrade dignity. The activity began with a pre-test to measure students’ initial understanding, followed by the screening of a short film illustrating the physical and psychological impacts of sexual violence. Subsequently, an interactive counseling session and open discussion were held to explore appropriate ways to respond to and report such incidents. The activity concluded with a post-test, showing an increase in students’ understanding from 69% to 90%. Challenges encountered included students’ reluctance to openly discuss the issue and the absence of accompanying teachers during the event. Nevertheless, the students’ enthusiasm and active participation demonstrated the program’s success in fostering awareness of the importance of self-protection and creating a safe, violence-free school environment.